2009
DOI: 10.1128/aac.01564-08
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Tamoxifen: In Vitro and In Vivo Activities and Mechanistic Characterization

Abstract: Tamoxifen (TAM), an estrogen receptor antagonist used primarily to treat breast cancer, has well-recognized antifungal properties, but the activity of TAM has not been fully characterized using standardized (i.e., CLSI) in vitro susceptibility testing, nor has it been demonstrated in an in vivo model of fungal infection. In addition, its mechanism of action remains to be clearly defined at the molecular level. Here, we report that TAM displays in vitro activity (MIC, 8 to 64 g/ml) against pathogenic yeasts (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 49 publications
(78 reference statements)
6
109
0
1
Order By: Relevance
“…Different research on mammalian cells and yeast clearly showed that TAM targets endoplasmic reticulum calcium pumps, protein kinase C, and/or CaM. Consequently, this targeting induces an increase in intracellular calcium as a non-estrogen receptor-dependent effect (18). Our in vitro results on the TAM effects suggest a calcium cell deregulation in treated protoscoleces (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Different research on mammalian cells and yeast clearly showed that TAM targets endoplasmic reticulum calcium pumps, protein kinase C, and/or CaM. Consequently, this targeting induces an increase in intracellular calcium as a non-estrogen receptor-dependent effect (18). Our in vitro results on the TAM effects suggest a calcium cell deregulation in treated protoscoleces (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…It has a wide range of effects on mammalian cell physiology, such as induction of intracellular calcium release, apoptosis, and autophagy. Moreover, it possesses antioxidant and antiangiogenesis properties (18). Consistent with this wide range of cellular effects, TAM has been shown to target mammalian proteins such as calmodulin (CaM), protein kinase C, phospholipase C, phosphoinositide kinase, P-glycoprotein (Pgp), and swelling-induced chloride channels (19).…”
mentioning
confidence: 94%
“…Indeed, trifluoperazine, pimozide, and other antipsychotics are well-characterized calmodulin inhibitors (26). Recently, we confirmed that tamoxifen targets calmodulin as part of its antifungal activity against S. cerevisiae (27). As detailed below, we have shown that a number of these molecules directly bind C. neoformans calmodulin, suggesting that this activity may contribute to the mechanism of their antifungal properties.…”
Section: Screen Of Prestwick Library Identifies Drug-like Molecules Withmentioning
confidence: 53%
“…Both of these approaches suggested that many of our hits may target calmodulin as part of their mechanism of action. Supporting that hypothesis was the fact that phenothiazines such as trifluoperazine, thioridazine, and prochlorpromazine are well-characterized, canonical calmodulin antagonists (26); similarly, tamoxifen, bepridil, and amiodarone have all been shown to inhibit mammalian calmodulin (27). Curiously, except for our previous studies supporting calmodulin as a target of tamoxifen in S. cerevisiae, the anticalmodulin properties of these drugs have not previously been invoked as a potential mechanism for their antifungal activity (27).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation